Regime Transformation From Below: Mobilization for Democracy and Autocracy From 1900 to 2021 - Sebastian Hellmeier; Michael Bernhard (Comparative Political Studies, 2023)
Mass mobilization (MM) is an important driver of political change. While some citizens organize in favor of more democratic institutions, others take to the streets to support an authoritarian status quo. This article introduces measures of pro-democratic and pro-autocratic MM using expert assessments for 179 polities from 1900–2021. The data allow us to trace patterns in MM over time, across regions and regime types. We use this new data to systematically analyze the relationship between both types of mobilization and regime change. We confirm the findings of the literature on contentious democratic politics, and our analysis of autocratic mobilization allows us to make sense of the controversy in the literature on “bad actors” in civil society. We show that MM in favor of autocracy negatively affects democracy, making a case for specifying the goals of the actors involved in contentious politics to more precisely understand their impact.
doi:10.7910/DVN/YQPN8D
Keywords: 320; democratization and regime change; social movements; quality of democracy; civil society; mass mobilization